2008
DOI: 10.1111/j.1462-2920.2007.01475.x
|View full text |Cite
|
Sign up to set email alerts
|

A metagenomic analysis of soil bacteria extends the diversity of quorum‐quenching lactonases

Abstract: A metagenomic library of 10,121 clones, generated from bacteria inhabiting a pasture soil from France, was screened for the presence of fosmids conferring either N-acylhomoserine lactone (NAHL) synthesis or NAHL degradation ability upon their Escherichia coli host. No clone producing NAHLs was identified whereas one, containing a 31 972 bp insert in fosmid p2H8, allowed NAHL degradation. This led to the cloning and identification of a gene, qlcA, encoding an NAHL-lactonase activity, as judged by lactone-ring c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 57 publications
1
63
0
Order By: Relevance
“…Despite their differences in DNA sequence and metal ion dependence ( Table 2), all of these enzymes were confirmed to function as lactonases following biochemical analysis of reaction products. Additionally, in vitro and in vivo studies have confirmed the overall value of these lactonases in quorum quenching and disease prevention against E. carotovora (62,68,71,72), akin to what was originally shown with AiiA.…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 87%
See 1 more Smart Citation
“…Despite their differences in DNA sequence and metal ion dependence ( Table 2), all of these enzymes were confirmed to function as lactonases following biochemical analysis of reaction products. Additionally, in vitro and in vivo studies have confirmed the overall value of these lactonases in quorum quenching and disease prevention against E. carotovora (62,68,71,72), akin to what was originally shown with AiiA.…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 87%
“…Metagenomic analyses faciliated the discovery of QlcA, BipB01, BipB04, BipB05, and BipB07 (68,74,75), and screens for AHL-degrading bacteria led to the identification of QsdA of Rhodococcus erythropolis strain W2 (70), AiiM of Microbacterium testaceum (71), AidH of Ochrobactrium sp. strain T63 (72), and QsdH of Pseudoalteromonas byunsanensis strain 1A01261 (73).…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 99%
“…Genes encoding AHL-acylase, which hydrolyzes the amide bond of AHL, have been cloned from Ralstonia spp., Anabaena spp., Streptomyces spp., Shewanella spp., and Pseudomonas aeruginosa. Novel AHLdegrading genes have been isolated from metagenomic libraries constructed from soil samples (19,22). Recently, it was reported that some members of the α/β hydrolase family have AHL-lactonase activity (11,30).…”
mentioning
confidence: 99%
“…Human and murine paraoxonase degrades AHL by hydrolyzing its lactone ring (21). Novel AHL lactonase genes have been isolated from a metagenomic library which was constructed from environmental soil samples (24,27). AHL-degrading genes have also been utilized in the biocontrol of plant diseases.…”
mentioning
confidence: 99%